Association of LEI0258 marker alleles and susceptibility to virulent Newcastle Disease Virus infection in Kuroiler, Sasso, and Local Tanzanian Chicken Embryos - Mpenda, Fulgence N.; Tiambo, Christian K.; Kyallo, Martina M.; Juma, John; Pelle, Roger; Lyantagaye, Sylvester L.; Buza, Joram (Hindawi Limited, 2020)
Newcastle disease (ND) control by vaccination and an institution of biosecurity measures is less feasible in backyard chicken in developing countries. Therefore, an alternative disease control strategy like the genetic selection of less susceptible chicken genotypes is a promising option. In the present study, genetic polymorphism of LEIO258 marker and association with susceptibility to virulent Newcastle disease virus (NDV) infection in Kuroilers, Sasso, and local Tanzanian chicken embryos were investigated. Samples from high (15%) and less (15%) susceptible cohorts were genotyped by sequencing of LEI0258 marker. A total of 75 DNA sequences comprised of 29 Kuroiler, 29 local Tanzanian chickens, and 17 Sasso were analyzed. Neighbor-joining phylogenetic trees were constructed to depict the clustering of LEI0258 marker alleles and relationship with susceptibility. Alleles with frequency ≥3 were considered for association with susceptibility by the use of the inference technique. The present findings suggest that some LEI0258 marker genetic polymorphisms apart from LEI0258 marker allelic based on sizes may be linked with chicken MHC-B haplotypes that confer chickens variability in resistance or susceptibility to infections. Furthermore, these results demonstrate the presence of relationship between LEI0258 marker polymorphisms and variations in chicken susceptibility to NDV infection, which could be utilized in breeding programs designed to improve chicken disease resistance.